A violence epidemic model to study trend of domestic violence, a study of tamale metropolis - Sebel, Charles; Otoo, Dominic (International Journal of Applied Mathematical Research, 2014)
There is a growing concern about the rise of violence on the streets and the media around the world, the possibility of an individual to be affected by violence at home is an undeniable reality facing most families around the globe. Domestic violence can take many forms including physical, psychological, sexual, and economic. It not only has devastating physical and psychological consequences on its victims, but can seriously damage the foundations of the family leading to its disintegration. There is therefore the need to find out the trend of spread in our communities, since it has the potential to slow down productivity in any society. The study used a simple continuous model for the spread of Domestic Violence, using Ordinary Differential Equations. A mathematical model is inspired from the spread of Domestic Violence in Tamale Metropolis in which the interaction of the widespread is likely to be minimized. A modeling technique of Abusive, Susceptible and Violence Victims (ASV), similar to the Susceptible, Infectious and Recovered (SIR) model in Epidemics, is used for formulating the spread of Domestic Violence as a system of Differential Equations. The system of Differential Equations is analyzed by linearization of nonlinear systems and non-dimensionlization to predict the behaviour of the spread of Domestic Violence.   Keywords: Abusive, domestic violence, epidemic model, infectious and recovered susceptible and violence victims.